Thermosensitive Chitosan-Based Injectable Hydrogel as an Efficient Anticancer Drug Carrier - Ahsan, Anam; Farooq, Muhammad Asim; Parveen, Amna (ACS omega, 2020)
A thermosensitive, physically cross-linked injectable hydrogel was formulated for the effective and sustained delivery of disulfiram (DSF) to the cancer cells as there is no hydrogel formulation available until now for the delivery of DSF. As we know, hydrogels have an advantage over other drug delivery systems because of their unique properties, so we proposed to formulate an injectable hydrogel system for the sustained delivery of an anticancer drug (DSF) to cancer cells. To investigate the surface morphology, a scanning electron microscope study was carried out, and for thermal stability of hydrogels, TGA (thermogravimetric analysis) and DSC (differential scanning calorimetry) were performed. The rheological behavior of hydrogels was evaluated with the increasing temperature and time. These developed hydrogels possessing excellent biocompatibility could be injected at room temperature following rapid gel formation at body temperature. The swelling index and in vitro drug release studies were performed at different pH (6.8 and 7.4) and temperatures (25 and 37 °C). The cell viability of the blank hydrogel, free DSF solution, and Ch/DSF (chitosan/DSF)-loaded hydrogel was studied by MTT assay on SMMC-7721 cells for 24 and 48 h, which exhibited higher cytotoxicity in a dose-dependent manner in contrast to the free DSF solution. Moreover, the cellular uptake of DSF-loaded hydrogels was observed stronger as compared with free DSF. Hence, chitosan-based hydrogels loaded with DSF possessing exceptional properties can be used as a novel injectable anticancer drug for the sustained delivery of DSF for long-term cancer therapy.